2015
DOI: 10.1002/wps.20187
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and cerebrovascular risk factors and events associated with second-generation antipsychotic compared to antidepressant use in a non-elderly adult sample: results from a claims-based inception cohort study

Abstract: This is a study of the metabolic and distal cardiovascular/cerebrovascular outcomes associated with the use of second-generation antipsychotics (SGAs) compared to antidepressants (ADs) in adults aged 18-65 years, based on data from Thomson Reuters MarketScan V R Research Databases 2006-2010, a commercial U.S. claims database. Interventions included clinicians' choice treatment with SGAs (allowing any comedications) versus ADs (not allowing SGAs). The primary outcomes of interest were time to inpatient or outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 48 publications
2
65
0
2
Order By: Relevance
“…In conclusion, this study identified that the reduction in racial/ethnic differences in antidepressant use after the box warning (caused by the decline among White youth and steady rates among Blacks and Latinos) was in large part explained by the fact that racial/ethnic minority youth largely seek care from a different subset of providers than White youth and that minority‐serving providers reacted differently to the box warning. As rates of psychotropic medication use in youth continue to climb in the United States, information about the long‐term risks of these medications has emerged eg, and will continue to challenge decision making for providers, youth living with mental illness, and their caregivers. Going forward, policy makers and prescribers should pay close attention to how these risk warnings are disseminated and the differential practice patterns of providers of youth of color, and target resources and provider education to lower the risk of adverse health outcomes faced by these vulnerable patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study identified that the reduction in racial/ethnic differences in antidepressant use after the box warning (caused by the decline among White youth and steady rates among Blacks and Latinos) was in large part explained by the fact that racial/ethnic minority youth largely seek care from a different subset of providers than White youth and that minority‐serving providers reacted differently to the box warning. As rates of psychotropic medication use in youth continue to climb in the United States, information about the long‐term risks of these medications has emerged eg, and will continue to challenge decision making for providers, youth living with mental illness, and their caregivers. Going forward, policy makers and prescribers should pay close attention to how these risk warnings are disseminated and the differential practice patterns of providers of youth of color, and target resources and provider education to lower the risk of adverse health outcomes faced by these vulnerable patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…We used the literature (e.g., (1316) and expertise within our research team (XX [anonymized for review]) to classify drugs. Since there is insufficient evidence on the impact of antipsychotic combinations on metabolic risk (e.g., are risks additive?…”
Section: Methodsmentioning
confidence: 99%
“…The strength of the evidence on the association between second-generation antipsychotics, the most widely used class of antipsychotics, and metabolic risk varies substantially by drug (e.g., (512)). However, the high metabolic risk associated with several of these drugs is incontrovertible (e.g., (1316). …”
Section: Introductionmentioning
confidence: 99%
“…, Haddad & Sharma , Correll et al . ). A large meta‐analysis comparing the efficacy and tolerability of 15 different antipsychotic drugs (Leucht et al .…”
Section: Physical Health Problems – the Risks Of Taking Antipsychoticsmentioning
confidence: 97%